THE EFFECTIVENESS OF CLUSTERING TECHNIQUE IN IMPROVING STUDENTS' NARRATIVE WRITING SKILL - Intan Nurcahya, - (2009)
The focus of this research is to investigate the effectiveness of clustering technique in improving students' narrative writing skill of the 60 second graders at SMU Negeri I Cianjur. It was aimed at finding out whether the clustering technique is effective or not in improving students' narrative writing skill. It also was aimed at finding out the advantages, the disadvantages and the students' response of using this kind of technique in improving students' narrative writing skill. Quasi experimental design was used to conduct this research. The samples of this study were students of XI IPA IV as the experimental group, and students of XI IPA X as the control group. The experimental group was given treatments using clustering technique, while the control group did not get the treatment. Data were collected from pre-test and post-test, questionnaire and interview. The independent t-test fromula were used to analyze the data from the tests. Meanwhile, the data from questionnaire and interview were analyzed to examine the advantages and the disadvantages of clustering technique and students' response about the use of clustering in improving their narrative writing skill. The research findings show that clustering technique is effective in improving students' narrative writing skill, especially in prewriting stages which involve the generating ideas process. Additionally, the results from questionnaire show that clustering technique has several advantages: (a) the clustering technique eased the students to understand the structure and features of narrative text; (b) it helped the students made a creative and systematical narrative story. However, the difficulties of choosing the proper vocabulary and the amount of time needed in the application of clustering technique become the disadvantages of this technique. This study is expected to give an alternative way of teaching and learning narrative writing.